Role of Dietary Antioxidants in Diabetes: An Overview - Shafras, M; Sabaragamuwa, R; Suwair, M (Elsevier BV, 2024)
Diabetes mellitus (DM) is a devastating medical condition which has become one of the top ten causes of most deaths, with a 70 % increase since 2000. DM is characterised by elevated plasma glucose levels. The excess glucose levels have been found to have a causal link with the development of reactive oxygen species leading to oxidative stress. Failure of the body's intracellular antioxidant system to compensate for increased oxidative stress results in the activation of stress-sensitive intracellular signalling pathways and ultimately cellular damage, which leads to the pathogenesis of DM. It is evident that naturally occurring dietary antioxidants such as vitamins E, A, and C, plant polyphenols, carotenoids, flavonoids, glutathione, alpha-lipoic acid, and polyamines all provide significant protection against diabetes. According to research, antioxidant therapy protects the beta-cell against oxidative stress-induced apoptosis, preserves beta-cell function, and reduces diabetic-related complications. As a result, the use of naturally occurring antioxidants has increased dramatically, not only because of their natural therapeutic effects, but also because of the safety concerns associated with synthetic antioxidants, as well as their affordability and availability. This paper compiled the current research on the role of oxidative stress in diabetes and the significance of natural dietary antioxidants in mitigating that effect.
Keywords: 3101 Biochemistry and Cell Biology; 32 Biomedical and Clinical Sciences; 31 Biological Sciences; Diabetes; Complementary and Integrative Health; Nutrition; 5 Development of treatments and therapeutic interventions; 5.1 Pharmaceuticals; Metabolic and endocrine